(untitled) (American Journal of Islam and Society, 2013)
As one of history’s most prolific Muslim writers, the theologian and jurist Ibn Hazm (d. 1064) had a remarkably successful intellectual career. Scholars continue to argue over him, perhaps due to his own diverse perspectives, potentials, and achievements. I consider his multiple achievements, notwithstanding any deserved negative impressions, a cause for celebrating this intellectual giant. Consequently, it is appropriate that he be profiled here. While this format may be restrictive, I hope to pursue some specific aspects in subsequent editorials to paint a more comprehensive and coherent picture of this multifaceted scholar. Charles Pellat, in his article on “Ibn îazm al-Andalus¥” writes: “Ab´ Muúammad ‘Al¥ ibn Aúmad ibn Sa‘¥d ibn îazm, a poet, man-of-letters, historian, polemist, juriconsult, theologian, logician, metaphysician, and psychologist, was certainly one of the most refined and productive representatives of the Arab culture in Spain.” ..